Functional Outcomes of Capitellum Fractures Treated by Open Reduction and Internal Fixation with Herbert Screw: A Descriptive Cross-sectional Study - KC, Kapil Mani (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: Based on the complex intra-articular nature of capitellum fractures, it has been sometimes difficult to formulate a universally accepted method of surgical treatment. The purpose of this study is to present the functional outcomes of capitellum fractures after fixation with Herbert screw including the safety and tips of the surgical approach. METHODS: This descriptive cross-sectional study was done from December 2014 to November 2019. Ethical approval was taken. The study included 22 capitellum fractures treated by open reduction and internal fixation with Herbert screws either lateral or anterolateral approach. Functional outcomes were assessed with Mayo elbow performance index scores at the latest follow-up visit. Convenient sampling was done. Data entry was done using the Statistical Package for the Social Sciences (version16.0). RESULTS: Out of 22 surgeries, the average time to unite the fracture was 11.13±1.20 weeks (range 9 to 15). The mean range of movement for flexion and extension was 138.41±8.22 degree while the mean supination and pronation range was 161.59±6.79 degree. The average time of follow-up in this series was 37.45±9.43 weeks (range 22 to 58 weeks). Similarly, the mean Mayo elbow performance index score at the latest follow-up was 90.22±8.65 (range 70 to 100). CONCLUSIONS: Careful assessment and radiological evaluation, anatomical reduction, and stable fixation with Herbert screws maintaining the minimal damage to the articular cartilage can maximize the functional outcomes and minimize the incidence of complications.